Error correction of a phase-only computer-generated hologram for an aspheric surface - Zhang H.; Yan Y.; Zhou H.; Qiao Y. J.; Si J.; Wang D. (Journal of the European Optical Society-Rapid Publications, 2014)
When applying phase-only computer-generated hologram (CGH) as a standard model of optical measurement in computer-generated holography for aspheric surface testing, it has the advantage of simplifying optical path configuration and improving the diffraction efficiency of the incoming light. However, errors always exists during the encoding process of fabricating multiphase level CGHs and this kind of errors will be amplified level by level in the measurement. According to the analysis of the encoding error, the error of CGH increases linearly when its quantified period increases. For example, if the quantified period is 32, the maximum of encoding error is 16.46 which can lead wave-front aberration 0.085λ of a secondary parabolic surface with 512×512 sampling pixels. In this article, an optimization method based on deviation of minimum boundary value has been used to eliminate the encoding error of CGH. In the experiment, we use a liquid crystal spatial light modulator to generate CGHs and measure residuals of reconstructed wave-front of a secondary parabolic surface. The measurement results show that average decrease of the RMS values of the residuals is 0.07 when their periods range from 3 to 6, which indicates the optimization method is effective.